2019
DOI: 10.1029/2019ms001870
|View full text |Cite
|
Sign up to set email alerts
|

The DOE E3SM Coupled Model Version 1: Description and Results at High Resolution

Abstract: This study provides an overview of the coupled high‐resolution Version 1 of the Energy Exascale Earth System Model (E3SMv1) and documents the characteristics of a 50‐year‐long high‐resolution control simulation with time‐invariant 1950 forcings following the HighResMIP protocol. In terms of global root‐mean‐squared error metrics, this high‐resolution simulation is generally superior to results from the low‐resolution configuration of E3SMv1 (due to resolution, tuning changes, and possibly initialization proced… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

15
276
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 204 publications
(319 citation statements)
references
References 168 publications
(272 reference statements)
15
276
0
Order By: Relevance
“…Hence, given a new protocol, together with model resolutions which range wider than those used in previous CMIP exercises, we need to assess the efficacy of this experimental design, finding its strengths and weaknesses, in addition to using it to assess the impact of model horizontal resolution. Similar assessments with other global climate models are ongoing and can be found in C. D. , Cherchi et al (2019), Voldoire et al (2019), Gutjahr et al (2019), Sidorenko et al (2019), Haarsma et al (2019) and Caldwell et al (2019).…”
Section: Introductionsupporting
confidence: 76%
“…Hence, given a new protocol, together with model resolutions which range wider than those used in previous CMIP exercises, we need to assess the efficacy of this experimental design, finding its strengths and weaknesses, in addition to using it to assess the impact of model horizontal resolution. Similar assessments with other global climate models are ongoing and can be found in C. D. , Cherchi et al (2019), Voldoire et al (2019), Gutjahr et al (2019), Sidorenko et al (2019), Haarsma et al (2019) and Caldwell et al (2019).…”
Section: Introductionsupporting
confidence: 76%
“…A high resolution will produce a much better AMOC system than the one by lower resolution in observations. For both CESM and E3SM, previous studies also indicate that the simulated Gulf Stream is much closer to the observed one in the 1/108 horizontal resolution version of the models than that in the standard 18 version (Bryan et al 2010;Small et al 2014;Caldwell et al 2019). Nevertheless, any detailed comparisons between model simulations and observations are complicated not only by the dependence of the details of the modeled AMOC including the Gulf Stream system and their biases on resolution, but also by the dependence of the details of the observed climatology on the resolution at which it is compiled (e.g., see Seidov et al 2019).…”
Section: Discussionmentioning
confidence: 66%
“…One of the pair prescribes the SST and sea ice concentration to represent current climate conditions. The other simulation is identical except for increasing the SST uniformly by 4 K. More details about the E3SMv1 Cess configuration are documented in Caldwell et al, (2019).…”
Section: Model Simulationsmentioning
confidence: 99%
“…Therefore, it is critical to ensure that the O3v2 scheme does not cause significant degradation of the simulated mean climate as well as the climate sensitivity. Here we apply the same diagnostic to examine the overall climate performance as used in the E3SMv1 overview papers (Golaz et al, 2019;Caldwell et al, 2019). In this diagnostic (Figs.…”
Section: Mean Climatementioning
confidence: 99%
See 1 more Smart Citation